TP53INP2 at the crossroad of apoptosis and autophagy in death receptor signaling - Ivanova, Saška (Mol Cell Oncol, 2019)
The binding of ligands to death receptors elicits distinct outcomes, such as apoptosis, inflammation and necroptosis, depending on the cellular context. We have recently described that the autophagic protein TP53INP2 favors apoptosis upon death receptor signaling and is a potential biomarker of responsiveness to TRAIL treatment.